2013
DOI: 10.1210/jc.2013-2061
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Insulin Reduces Olfactory Sensitivity in Normosmic Humans

Abstract: These findings suggest that intranasal insulin impairs olfactory sensitivity for a nonfood odorant, whereas no such effects were found for olfactory discrimination. Thus, variations in brain insulin signaling most likely have implications for the olfactory threshold of normosmic humans. Bearing in mind the fact that insulin acts as an anorexigenic signal in the human brain, further studies are needed to test whether intranasal insulin also impairs the ability of humans to perceive food-related odors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 24 publications
3
60
1
1
Order By: Relevance
“…reduces odor sensitivity for the nonfood odorant n-butanol in normosmic subjects (25). Thus, at first glance, our finding that acute intranasal insulin (40 I.U.)…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…reduces odor sensitivity for the nonfood odorant n-butanol in normosmic subjects (25). Thus, at first glance, our finding that acute intranasal insulin (40 I.U.)…”
Section: Discussionmentioning
confidence: 65%
“…(25). This suggests that human odor processing is sensitive to acute fluctuations of CNS insulin concentration.…”
mentioning
confidence: 99%
“…However, intranasal insulin was found to reduce sensitivity to the odorant n-butanol (i.e. increased threshold concentration), but not olfactory discrimination, in normosmic subjects receiving 40 IU of insulin intranasally (zinc concentration not specified; Brünner et al, 2013). …”
Section: Discussionmentioning
confidence: 98%
“…Here, associations with activity of the fusiform gyrus 50 and further brain areas, including the hippocampus, were detected. 42,50,62 In addition to the effect of insulin on perception, two studies 63,64 have reported that insulin attenuates smelling capacity in humans. Thus, insulin reduces the response to food cues and smelling capacity in lean people, a reac tion that could physiologically regulate eating behaviour in a postprandial state when high insulin levels prevail.…”
Section: Brain Insulin and Cognitive Functionmentioning
confidence: 99%